2017
DOI: 10.1080/03007995.2017.1346595
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular event incidence and cost in type 2 diabetes mellitus: a Medicare claims-based actuarial analysis

Abstract: Cardiovascular events in Medicare fee-for-service beneficiaries with T2DM contribute substantially to Medicare cardiovascular events, resource utilization, and cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…More than 10% of these patients had diabetes-related complications at baseline, which indicates that people may have had diabetes-related complications prior to receiving a diagnosis of diabetes. In general, our estimates are higher than those in epidemiology data published in developed countries, including the UK [21], the USA [22], and Germany [23], even given the similar or even younger mean ages in these study populations. Definitions and/or diagnoses criteria of complications were not standardized in these earlier study, which is why we clarified the identification process in detail, including the ICD codes and primary or secondary diagnoses criteria we used.…”
Section: Discussioncontrasting
confidence: 87%
“…More than 10% of these patients had diabetes-related complications at baseline, which indicates that people may have had diabetes-related complications prior to receiving a diagnosis of diabetes. In general, our estimates are higher than those in epidemiology data published in developed countries, including the UK [21], the USA [22], and Germany [23], even given the similar or even younger mean ages in these study populations. Definitions and/or diagnoses criteria of complications were not standardized in these earlier study, which is why we clarified the identification process in detail, including the ICD codes and primary or secondary diagnoses criteria we used.…”
Section: Discussioncontrasting
confidence: 87%
“…27 In line with our study, the differences between the two cohorts were minimal. A study in the USA 40 found that the total average cost was 2.2 times higher in patients with T2DM versus non-DM. However, although the incidence of vascular complications was higher in the T2DM group, the average cost per CV event was similar between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the pain, suffering and inconvenience to the affected individual, there is also a significant financial burden of T2DM both for the individual and for society. Cost-of-illness studies in different regions show that the medical expenses for people with T2DM are 2-to 4-fold higher than for people not suffering from this condition (4)(5)(6) . For example, about 10 % of healthcare expenses in Germany are spent on the medical care of people with T2DM.…”
mentioning
confidence: 99%